A CASE OF SUCCESSFUL USE OF PERCUTANEOUS TEMPORARY OCCLUSION OF THE HEART VENOUS SINUS IN PATIENT WITH ACUTE CORONARY SYNDROME WITH ST SEGMENT ELEVATION IN THE ABSENCE OF HEMODYNAMICALLY SIGNIFICANT ATHEROSCLEROTIC LESIONS OF THE CORONARY ARTERIES - B. E. Shakhov; E. B. Shakhov; E. B. Petrova; E. G. Sharabrin; E. V. Chebotar (Креативная хирургия и онкология, 2017)
The search for new methods of adequate antegrade blood flow restoration in the coronary arteries of patients with acute coronary syndrome with ST-segment elevation (ACSesST) without hemodynamically significant atherosclerotic lesions of the coronary arteries is a poorly studied item. The author gives the clinical example of a patient with ACSesST without hemodynamically significant atherosclerotic lesions of the coronary arteries and deceleration of antegrade blood flow in the area of the anterior descending artery (ADA). Percutaneous temporary occlusion of the coronary sinus was done to the patient during 10 minutes in the balloon catheter «inflation-deflation». The procedure resulted in a positive impact on coronary hemodynamics such as distal coronary spasm cupping, myocardial perfusion improvement and restoration of adequate antegrade blood flow in the pool ADA.